A study on level of awareness and knowledge about waqf among academy of contemporary islamic studies students / Muhammad Adeeb Mohd Ali Bahari. - Mohd Ali Bahari, Muhammad Adeeb (2019)
Waqf literally means to prevent or to restrain or to abstain. Waqf according to Islam means devoting something for the cause of Allah or the basic purpose is good task for Allah. The study aims to identify the level of awareness and knowledge among ACIS students. In general, students are aware about the concept of waqf but some of them are still low on their level of knowledge about waqf. The issue here is on the level of knowledge among Islamic studies student are low although it is crucial for students to masterty the knowledge pertaining waqf. A quantitative study was conducted using survey questionnaire to further investigate the above mentioned issue. Therefore, the students must gain their knowledge and aware about concept of waqf and implement waqf in their life.